PENGARUH KONSERVATISMA AKUNTANSI TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL PEMODERASI - Intan Soraya (Diponegoro Journal of Accounting, 2014)
The aim of this research is to analyze the effect of accounting conservatism to the practice of earnings management by adding a moderating variable which is managerial ownership. Unlike the previous researches, manufacture companies listed in Bursa Efek Indonesia are utilized as sample in this research. The samples were collected using purposive sampling method. There are 32 companies listed in the stock exchange during 2010 – 2012 which become the samples in this research.  This research employs simple and double regressive method as data processing means. Variables used in this research are accounting conservatism as independent variables, earnings management as dependent variable, and managerial ownership as moderating variable. This research utilizes C-Score in measuring conservatism and Healy model (1985) to determine the practice of earnings management. Data processing results show that accounting conservatism significantly affects earnings management by negative trends. However, managerial ownership is shown to be able to moderate the influence of accounting conservatism toward earnings management practices.